The Hippo pathway regulates human megakaryocytic differentiation - Lorthongpanich, Chanchao; Jiamvoraphong, Nittaya; Supraditaporn, Kantpitchar; Klaihmon, Phatchanat; U-pratya, Yaowalak; Issaragrisil, Surapol (Thrombosis and Haemostasis, 2017)
The Hippo pathway is involved in several biological processes in both flies and mammals. Recent studies have shown that the Hippo pathway regulates Drosophila’s haematopoiesis; however, understanding of its role in mammalian haematopoiesis is still limited. In flies, deletion of the Hippo component gene, Warts, affects crystal cell differentiation. We explored the role of the Hippo pathway in human haemato-poiesis focusing on megakaryopoiesis. To investigate the role of LATS1/2 (a mammalian homolog of Warts) in human megakaryo -blastic cell differentiation and platelet formation, megakaryoblastic cell (MEG-01) line was used as a model to gain insight into mechan-ism of the Hippo pathway in mammalian megakaryopoiesis. Effect of LATS1/2 on megakaryoblastic cell differentiation and platelet production were determined by functional changes. We found that depletion of LATS1/2 resulted in an increase of CD41+ megakaryocytes with impaired platelet biogenesis. Our study shows that the Hippo signalling pathway plays a crucial role in human megakaryoblastic cell differentiation and thrombopoiesis.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Hippo pathway; LATS1/2; megakaryocyte; platelet; thrombopoiesis